2016
DOI: 10.1186/s41240-016-0005-0
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic variations of gonad development of an air-breathing fish, Channa striata in the lentic and lotic environments

Abstract: The study was conducted to know the cyclic changes in gonadal maturation and to investigate the developmental stages of oocytes and testicular germ cells of an air-breathing fish, Channa striata. Fish were sampled monthly from lentic and lotic environments of three geographical locations of Bangladesh from December to November and the histological analysis of their gonad was done to evaluate the objectives. The highest mean GSI was 5.95 ± 0.20 for female in July and 0.14 ± 0.01 for male also in July showing th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 9 publications
0
11
1
1
Order By: Relevance
“…In contrast to our reports, Al Mahmud et al (2016) reported the minimum GSI value during the month of September and higher values from April to July for female Channa striata . Similarly, highest values of GSI were recorded during April- July in Channa bleheri (Rinku et al, 2013) and during May - August in C. punctatus (Sunita et al, 2011, Lalta et al, 2011).…”
Section: Resultscontrasting
confidence: 99%
See 2 more Smart Citations
“…In contrast to our reports, Al Mahmud et al (2016) reported the minimum GSI value during the month of September and higher values from April to July for female Channa striata . Similarly, highest values of GSI were recorded during April- July in Channa bleheri (Rinku et al, 2013) and during May - August in C. punctatus (Sunita et al, 2011, Lalta et al, 2011).…”
Section: Resultscontrasting
confidence: 99%
“…These different stages corresponded with those described macroscopically for M. montanus (Arockiaraj et al, 2004). However, microscopic examination of ovary sections reported by Al Mahmud et al (2016) revealed four stages of maturity in striated snakehead, Channa striata . The female fish showed significant (P < 0.05) weight changes in the ovaries corresponding to the three gametogenic stages (pre-spawning, spawning and post spawning) during different months of the year (Table 2).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Survival of any of these species in various seasonally changing environments depends on the development of mechanisms that permit it to adjust physiological functions to changes in that environment (Adriaenssens, Damme, Seebacher, & Wilson, ). Information regarding reproductive cycling and the relation of this cycling to the environment is very important for understanding the biology of a species as well as for scientific management of a fishery resource (Al Mahmud et al, ). Reproductive activities in most animals undergo cyclic changes and the patterns of these changes in the gonads are characteristics for each species (Lagler, Bardachi, Miller, & Passino, ).…”
Section: Introductionmentioning
confidence: 99%
“…BioMed Central and KOSFAS has been working hard for the last few months to publish the first FAS articles in 2016 and these first articles will cover the topics on fish reproduction physiology (Mahmud et al 2016), fish nutrition (Yun et al 2016), fish disease , and analytical chemistry in food sciences (Kim et al 2016). Fisheries and Aquatic Sciences will continue to publish articles on these topics and more as part of BioMed Central.…”
mentioning
confidence: 99%